Management of Patients undergoing Elective Craniotomy under Antiplatelet or Anticoagulation Therapy: An International Survey of Practice - Greuter, Ladina; Rychen, Jonathan; Chiappini, Alessio; Mariani, Luigi; Guzman, Raphael; Soleman, Jehuda (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background The literature concerning the management of antiplatelet (AP) and anticoagulation (AC) medication in the perioperative phase of craniotomy remains scarce. The aim of this international survey was to investigate the current practice among neurosurgeons regarding their perioperative management of AP and AC medication.Methods We distributed an online survey to neurosurgeons worldwide with questions concerning their perioperative practice with AP and AC medication in patients undergoing craniotomy. Descriptive statistics were performed.Results A total of 130 replies were registered. The majority of responders practice neurosurgery in Europe (79%) or high-income countries (79%). Responders reported in 58.9 and 48.8% to have institutional guidelines for the perioperative management of AP and AC medication. Preoperative interruption time was reported heterogeneously for the different types of AP and AC medication with 40.4% of responders interrupting aspirin (ASA) for 4 to 6 days and 45.7% interrupting clopidogrel for 6 to 8 days. Around half of the responders considered ASA safe to be continued or resumed within 3 days for bypass (55%) or vascular (49%) surgery, but only few for skull base or other tumor craniotomies in general (14 and 26%, respectively). Three quarters of the responders (74%) did not consider AC safe to be continued or resumed early (within 3 days) for any kind of craniotomy. ASA was considered to have the lowest risk of bleeding. Nearly all responders (93%) agreed that more evidence is needed concerning AP and AC management in neurosurgery.Conclusion Worldwide, the perioperative management of AP and AC medication is very heterogeneous among neurosurgeons.
Keywords: international survey; craniotomy; antiplatelet medication; anticoagulation